1988
DOI: 10.1111/j.1365-2672.1988.tb01880.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance among coliforms and Pseudomonas spp. from bodies of water around Port Harcourt, Nigeria

Abstract: Samples from municipal waste water, the Bonny River estuary and wells in and around Port Harcourt were examined for bacteriological quality over a 9 month period. A total of 157 Pseudomonas spp., 133 Escherichia coli and 282 other coliforms were isolated and tested for the incidence of resistance to 10 antibiotics. All of the Pseudomonas spp. were resistant to at least one of the antibiotics while 96.2% were resistant to two or more. Most (83.5%) of the E. coli and other coliforms (91.8%) were resistant to at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…They found that 90% of all isolates were resistant to one or more antibiotics. In another study, investigators showed that 80% of strains from municipal waste, river and estuarine water displayed antibiotic resistance 31) . Much lower resistance, ranging from 31 to 75%, has been reported for E. coli isolates from various aquatic environments 9,10,24) .…”
Section: Resultsmentioning
confidence: 99%
“…They found that 90% of all isolates were resistant to one or more antibiotics. In another study, investigators showed that 80% of strains from municipal waste, river and estuarine water displayed antibiotic resistance 31) . Much lower resistance, ranging from 31 to 75%, has been reported for E. coli isolates from various aquatic environments 9,10,24) .…”
Section: Resultsmentioning
confidence: 99%
“…13,14,27 Furthermore, the cattle are given water to drink from different communities while traversing from one region to the other; therefore, they are also exposed to different sources of water, including wells, streams, and rivers, which may be a reservoir of resistant organisms. 32 PFGE is considered the ''gold-standard'' for molecular typing of most bacteria and provides consistent results, as the method has been standardized and is an efficient tool for epidemiological investigations. 29,35 PFGE analysis of the MDR E. coli revealed a genetically diverse population; high genetic diversity among animal E. coli has been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…All FC strains analysed were susceptible to gentamycin. This antibiotic has often been described as an effective aminoglycoside towards E. coli (Al-Jebouri & Al-Meshhadani 1985;Sokari et al 1988).…”
Section: Discussionmentioning
confidence: 99%